Uterine carcinosarcomas case series of rare uterine malignancy - Patel, Jitendra; Pant, Punita; Shewalkar, Balaji; Meshram, Dhiraj (International Journal of Research in Medical Sciences, 2025)
Primary malignant mixed Müllerian tumor (MMMT) of the ovary is a rare and highly aggressive neoplasm predominantly affecting postmenopausal women. MMMT is a biphasic tumor comprising both epithelial and mesenchymal components and is associated with significantly higher mortality compared to epithelial ovarian neoplasms. Patients typically present with symptoms such as vaginal bleeding, abdominal pain, and a palpable mass. Surgery remains the primary treatment modality, while adjuvant therapies, including chemotherapy and radiotherapy, play a crucial role in improving locoregional control and managing distant metastasis. Due to the rarity of these tumors, there is limited literature on their optimal therapeutic management. This series aims to analyse the clinical presentations and treatment outcomes of patients diagnosed with this uncommon uterine cancer treated at our hospital.